2003
DOI: 10.1037/0096-3445.132.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Prospect relativity: How choice options influence decision under risk.

Abstract: In many theories of decision under risk (e.g., expected utility theory, rank dependent utility theory, and prospect theory) the utility or value of a prospect is independent of other prospects or options in the choice set. The experiments presented here show a large effect of the available options set, suggesting instead that prospects are valued relative to one another.The judged certainty equivalent is strongly influenced by the options available. Similarly, the selection of a preferred option from a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
119
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 95 publications
(155 reference statements)
14
119
1
Order By: Relevance
“…Some researchers argue instead that these effects are due to a human inability to represent absolute magnitudes, whether perceptual variables, utilities, payoffs, or probabilities [28,46]. The most recent type of comparative theories assumes that people make judgments and decisions 13 without consulting a utility scale based on the absolute magnitudes of stimuli (even for key ‗economic' variables such as time and probability) [13].…”
Section: Type Iii: Comparison-based Decision Making Without Value Commentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers argue instead that these effects are due to a human inability to represent absolute magnitudes, whether perceptual variables, utilities, payoffs, or probabilities [28,46]. The most recent type of comparative theories assumes that people make judgments and decisions 13 without consulting a utility scale based on the absolute magnitudes of stimuli (even for key ‗economic' variables such as time and probability) [13].…”
Section: Type Iii: Comparison-based Decision Making Without Value Commentioning
confidence: 99%
“…For example, the perceived value of a risky prospect (e.g., -p chance of x‖) is relative to other prospects with which it is presented, which is known as ‗prospect relativity' [28]. In particular, when judging the value of ‗50% chance of winning £200' and respondents have options of £40, £50, £60, and £70, the most popular choice is £60.…”
Section: Box 1 Psychological Evidence In Support Of Comparison-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…Beauchamp et al (2012), Birnbaum (1992), and Stewart et al (2003) found that when valuing a risky gamble, people were influenced by the range and skew of the options available as potential valuations. For example, Birnbaum (1992) valuation of a target gamble was higher when people selected a valuation from a negatively skewed set than from a positively skewed set.…”
Section: Malleability Of Risky and Delayed Choicesmentioning
confidence: 99%
“…Benartzi and Thaler (2001) account for this pattern with the 1/n heuristic, which assumes people place equal funds into each option, but the allocation is also compatible with the rank hypothesis. Stewart et al (2003) examine a laboratory analogue, where people are offered either five risky options or five safe options. Participants in the different conditions behaved as though they had different levels of risk aversion, even though participants were randomly assigned to different groups.…”
Section: Malleability Of Risky and Delayed Choicesmentioning
confidence: 99%